Hourglass procedure for combining ecosystem based adaptation and agroecology - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
A critical innovation at the centre of a GIZ policy paper setting out in simple steps how to achieve the complex task of linking agroecology and ecosystem-based adaptation across scales. This brings together two often separate communities with agricultural and environmental origins that are more effective when acting in concert.